2009
DOI: 10.1002/ejic.200901042
|View full text |Cite
|
Sign up to set email alerts
|

2,3,5,6‐Tetrafluoro‐p‐phenylenebis(phosphanes) – Preparation and Structure of an Electron‐Poor P–RF–P Linker

Abstract: A general synthetic access to functional 2,3,5,6‐tetrafluoro‐p‐phenylenebis(phosphanes) is presented, which should open the way to linear phosphorus‐based conjugated systems incorporating an electron‐deficient aryl moiety. 1,4‐Bis[bis(diethylamino)phosphanyl]‐2,3,5,6‐tetrafluorobenzeneand 1,4‐bis(dichlorophosphanyl)‐2,3,5,6‐tetrafluorobenzene have been synthesized in good yields and were characterized by spectroscopic methods and X‐ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The Pd–P contacts are 2.322(1) Å and 2.355(1) Å and thus in the upper range of Pd–P distances for this class of compounds 42. Compared with C 6 F 5 P(N i Pr 2 ) 2 [1.683(3) Å/1.669(4) Å]6 and p -C 6 F 4 [P(NEt 2 ) 2 ] 2 [1.675(2) Å/1689(2) Å]43 the P–N bonds in 3 are shortened upon coordination to the metal center [1.646(2) Å–1.662(2) Å], whereas the P–C bond is essentially unaffected. In contrast, the crystal structure of tris(pentafluorophenyl)phosphane derivative[(C 6 F 5 ) 3 P] 2 PdCl 2 shows much shorter Pd–P and Pd–Cl distances [2.291(1) Å and 2.305(1) Å, respectively], and the palladium center shows an almost planar coordination geometry 44.…”
Section: Resultsmentioning
confidence: 99%
“…The Pd–P contacts are 2.322(1) Å and 2.355(1) Å and thus in the upper range of Pd–P distances for this class of compounds 42. Compared with C 6 F 5 P(N i Pr 2 ) 2 [1.683(3) Å/1.669(4) Å]6 and p -C 6 F 4 [P(NEt 2 ) 2 ] 2 [1.675(2) Å/1689(2) Å]43 the P–N bonds in 3 are shortened upon coordination to the metal center [1.646(2) Å–1.662(2) Å], whereas the P–C bond is essentially unaffected. In contrast, the crystal structure of tris(pentafluorophenyl)phosphane derivative[(C 6 F 5 ) 3 P] 2 PdCl 2 shows much shorter Pd–P and Pd–Cl distances [2.291(1) Å and 2.305(1) Å, respectively], and the palladium center shows an almost planar coordination geometry 44.…”
Section: Resultsmentioning
confidence: 99%
“…14 Aiming at high rigidity, mainly aryl bonded oxophosphorane units have been employed as ligands so far, which are accessible via metallation reactions under inert conditions only, imposing some synthetic challenges with respect to organofluorine functionalities. 15,16 For alkyl bonded phosphonic acids the Michaelis-Arbuzov rearrangement provides a well-established access offering large structural variety. 17 A disadvantage of this reaction are usually very long reaction times and sometimes very poor yields following classical procedures.…”
mentioning
confidence: 99%
“…Gaseous HCl was prepared in situ by dropping neat H2SO4 to CaCl2 powder, bubbled through H2SO4 then through the reaction mixture and ultimately through a NaHCO3 outlet bubbler to neutralize excess HCl. Ch(TMS)2 (Ch = S, Se) 27 and Ar*PCl2 [28][29][30][31] were made following known literature procedures. CuCl, AgOTf, (Me2S)AuCl, and DMAP were purchased from Sigma Aldrich and used as received.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Alternatively, monomerization of 1S could be induced through the addition of 1,3-isopropyl-4,5-dimethylimidazol-2-ylidene (NHC), which resulted in the formation of the adduct 5S even without heating. 24 Taking our lead from these results, the reaction of DMAP with 1S in 2:1 stoichiometry yielded one major product in the 31 Although the ring expansion product was the only species obtained from the reaction between 1S and DMAP, the analogous reaction using 1Se gave numerous products, as determined by 31 P{ 1 H} NMR spectroscopy. Even though none of these products could be isolated and characterized, the NMR spectroscopic data clearly indicated that ring expansion to 2Se did occur (P = 88).…”
Section: Synthesis Of 7seagmentioning
confidence: 97%
See 1 more Smart Citation